Ethnobotanical Survey of Antidiabetic Medicinal Plants Used by Patients Visiting Health Facilities in the SALÉ Region (Morocco) - Youssef S'HIH; Ibrahim Hinad; Abdechahid Loukili; Moulay Laarbi Ouahidi (Traditional and Integrative Medicine)
Herbal medicine (HM) is frequently used by diabetic patients in Morocco, although limited information exists about the specific plants used by diabetic patients in the SALÉ region. This study aims to collect a list of plant species used by diabetic patients as traditional remedies. This study is based on an ethnobotanical survey. It was carried out using questionnaires with a sample of 300 diabetic patients visiting the health centres in SALÉ. The results indicate that 93% of type 2 diabetic patients and 7% of type 1 diabetic patients use HM alongside modern medications. Patients justify their use of HM due to its easy accessibility (34.3%), greater efficacy (27.7%), and low cost (27%). The majority (60.3%) are unable to specify the dosage used, and 95.3% are unaware of the toxicity of the plants. This study identified 32 medicinal plant species from 18 botanical families, with the most commonly used plants being Olea europea L. (9.3%), Coriandrum sativum L. (7.7%), Trigonella foenum-graecum L. (7.3%), Marrubium vulgare L. (6%), Lepidium sativum L., Lawsonia inermis L., Capparis spinosa L. (5.7%), and Artemisia absinthium (5%). The most used plant parts are leaves (40%) and seeds (23.67%); with infusion and decoction being the preferred preparation methods for oral administration. The findings indicate that the SALÉ region has a wide range of HM knowledge for treating diabetes, which needs further scientific study. This knowledge can serve as a foundation for pharmacological studies to assess the antidiabetic effects of these plants.